169 Examining the Associations Between Frailty, Obesity and Allostatic Load in The Irish Longitudinal Study on Ageing (TILDA). (16th September 2019) - McCarthy, Kevin; McNicholas, Triona; Laird, Eamon; Ward, Mark; Romero-Ortuño, Roman; Anne Kenny, Rose
Abstract: Background: Fried's frailty phenotype is defined by five criteria: exhaustion, unexplained weight loss, weakness, slowness and low physical activity. Frailty can also affect obese people. Little is known about how body mass index [BMI] or waist-hip ratio [WHR] are associated with frailty or pre-frailty in the face of confounding factors, including markers of allostatic load which are known to be involved in frailty biology. We cross-sectionally examined these associations in a population-based study. Methods: A cross-sectional analysis of data collected at Wave 1 (2010) of TILDA was undertaken. Participants aged <50 and those who did not have measurements of their BMI, WHR, chronic disease status, HbA1c, CRP, sex and educational status were excluded. Two multivariate logistic regression models (one with BMI and another one with WHR as measure of obesity) were computed adjusting for these covariates, with frail/pre-frail versus non-frail as the outcome variable. Results: 4, 568 participants were included: 3, 277 non-frail and 1, 291 frail/pre-frail. The frail/pre-frail group had a mean BMI of 29.2 (versus 28.3) kg/m 2 and a mean WHR of 0.912 (versus 0.899). In the adjusted regression model, BMI had a significant association with frailty/pre-frailty (OR 1.02, 95% CI: 1.01-1.04, p=0.001). However, in the model using WHR, the latter had a stronger association with frailty (OR 4.52, 95% CI: 1.60-12.72, p=0.004). In both models, age, education, chronic disease status, HbA1c and CRP had the expected associations with frailty/pre-frailty. Female sex was significantly associated with frailty/pre-frailty in the WHR model (OR 1.26, 95% CI 1.06-1.50, p=0.008). Conclusion: While obesity is associated with frailty, the distribution of body fat may be more important as a marker of frailty. These physical traits should not be overlooked in the over 50 population. The association between frailty, obesity and markers of 'inflammaging' could be examined longitudinally to further understand their complex biology.